x^3-3x^2+3x-1=(1-x)(5-3x)
(х-1)^3-(1-x)(5-3x)=0
(х-1)^3+(x-1)(5-3x)=0
(x-1)(x^2-2x+1+5-3x)=0
(x-1)(x^2-5x+6)=0
1. х-1=0
х=1
2. x^2-5x+6=0
По теореме Виета:
х=2, х=3
8+2√7 3+√7
√() - √( ) * √2 =
8-2√7 3-√7
избавимся от иррациональности в знаменателе
(8+2√7)*(8+2√7 ) (3+√7)*(3+√7)
√( ) - √( ) * √2 =
(8-2√7)*(8+2√7 ) (3-√7)*(3+√7)
(8+2√7)² ( 3+√7)²
√( ) - √( ) * √2 =
8²-(2√7)² (3²-√7²)
(8+2√7)² ( 3+√7)²
√( ) - √( ) * √2 =
64- 28 9 --7
(8+2√7)² ( 3+√7)²
√( ) - √( ) * √2 =
36 2
8+2√7 3+√7
- ( ) * √2 =
6 √ 2
2(4+√7) 4+√7 4+√7 -9-3√7
- ( 3+√7) = - ( 3+√7) = =
6 3 3
-5-2√7
=
3
x^3-3x^2+3x-1=(1-x)(5-3x)
(х-1)^3-(1-x)(5-3x)=0
(х-1)^3+(x-1)(5-3x)=0
(x-1)(x^2-2x+1+5-3x)=0
(x-1)(x^2-5x+6)=0
х-1=0
х1=1
x^2-5x+6=0
по теореме Виета: х2+х3=5, х2*х3=6 => х2=2, х3=3
ответ: х1=1, х2=2,х3=3